Pembinaan Cara Pengemasan Dan Pemasaran Produk Agar Terlihat Lebih Menarik Di desa Pasar Pedati kecamatan Pondok Kelapa Kabupaten Bengkulu Tengah - Azuwandri, Azuwandri; Charolina, Ovita; Hidayat, Rahmat Al; Hartono, Rudi; Akmal, Samsul (STIA Bengkulu, 2022)
The purpose of this activity is to encourage UMKM members so that they can market their products well. Thus increasing the income of UMKM actors. The target of this activity is the community of Pasar Pedati village, Central Bengkulu Regency, especially for small and medium businesses. The method used is the instruction on how to package the product in an attractive way to increase its selling value and how to market the product in the supermarket. From this training, the community and UMKM members find it very helpful and able to apply what they have learned from the training and can start marketing their products not only in the village but also at the local level, but also supermarket level.